2020
DOI: 10.3390/atmos11030235
|View full text |Cite
|
Sign up to set email alerts
|

Homogeneity of the Temperature Data Series from ERA5 and MERRA2 and Temperature Trends

Abstract: The stratosphere and its dynamics are a very important part of atmospheric circulation. We need to analyze its climatology, as well as long-term trends. A long-term trend study needs homogenous datasets without significant artificial discontinuities. The analysis is based on the two newest released reanalyses, Modern Era-Retrospective Analysis (MERRA2) and European Center for Medium-Range Weather Forecast Reanalysis (ERA5). The aim of this study is to detect discontinuities in the temperature time series from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…On the global scale, Poli et al (2016) compared the temperature data on the ERA-20C with the observation and demonstrated that the reanalysis data was 1K colder than the night observational data within 65 °north-south latitude. Kozubek et al (2020) indicated that the trend of temperature from ERA5 data has good consistency with observations data. Liu et al (2021) confirmed that the land surface temperature data on ERA5 products are highly consistent with the trend derived from satellite data in 2003-2017.…”
Section: Introductionsupporting
confidence: 64%
“…On the global scale, Poli et al (2016) compared the temperature data on the ERA-20C with the observation and demonstrated that the reanalysis data was 1K colder than the night observational data within 65 °north-south latitude. Kozubek et al (2020) indicated that the trend of temperature from ERA5 data has good consistency with observations data. Liu et al (2021) confirmed that the land surface temperature data on ERA5 products are highly consistent with the trend derived from satellite data in 2003-2017.…”
Section: Introductionsupporting
confidence: 64%
“…If we look at the trend comparison, the biggest differences can be found for 1 hPa, but for the lower pressure levels the main features are similar even when the amplitude is different. We also analyze a comparison of two reanalyses with GPS RO for the limited period 2010-2020, see [26]. From the comparison of two main reanalyses for a longer period and with GPS RO for a shorter period, we can say that at least down from 10 hPa ERA5 is suitable for our analysis.…”
Section: Resultsmentioning
confidence: 99%
“…In each grid, all three tests estimate only one main discontinuity, so this procedure is not able to detect multiple discontinuities. The homogeneity tests used in this paper have been widely used in climatological research, particularly for precipitation and temperature analysis [17,18,[29][30][31][32], therefore, we assume their usability also for ozone studies. We are interested primarily in the share of grids with discontinuity to all grids.…”
Section: Methodsmentioning
confidence: 99%